A Comparison of the Usage of Different Approaches for the Management of Plant Engineering Projects - Akbulut, Akin; Laroque, Christoph; Wenzel, Sigrid; Jessen, Ulrich (Proceedings of the 2015 Winter Simulation Conference)
Customized planning, engineering and construction of one-of-a-kind products (like wind energy, biogas or power plants) are complex and contain a lot of risks and temporal uncertainties, e.g. of logistics and project schedules. Therefore the management of this kind of projects has to be supported by adequate methods for the estimation of project risks and uncertainties. Based on the results of the joint research project simject of the Universities of Paderborn and Kassel, which aims at the development of a demonstrator for simulation-based and logistic-integrated project planning and scheduling, this paper discusses the usage of different approaches for supporting project management of plant engineering projects. After a short introduction and description of the approaches to be compared a wind energy plant as evaluation model as well as the application of the different methods are presented. Additionally, the usage of the approaches is compared and the advantages and disadvantages are pointed out.